Assessing the Effects of the Accounting Information System under the Enterprise Resources Planning - W. Chesoli, Dr. Joshua (IJRDO - Journal of Business Management, 2017)
This study aimed to identify the effectiveness of the accounting information system for companies that adopting "Enterprise Resource Planning (ERP)" systems, and its relationship with the quality of accounting outputs (information) and the internal control. To achieve the goal of this study, the researcher chooses particularly companies that use ERP systems. A questionnaire designed and distributed to a sample of accountants and financial managers who works at such companies. The researcher used means and frequencies to describe the sample of the study and the questionnaire responses besides t test to test the hypotheses of this study. The results showed that the integration of accounting information system within the ERP system improving the quality of accounting outputs and the internal control in companies. More studies are required on this field to support the result of current study and to expand the accounting literature on this issue. Companies also recommended to adopt ERP systems because it will improve their performance.